Interactive electronic placard as a means of collective education of a new format - Кисельова, О. Б.; Брославська, Г. М. (Scientific notes of the pedagogical department, 2019)
The article focuses on the relevance of the development and the use of interactive placards as means of collective education of a new format. Its definition is considered, and features are presented that distinguish it from other electronic educational resources. It is proved that the use of interactive placards allows not only individualization of education within the general educational process, but also promotes the formation of cooperation skills. In the process of teaching using interactive electronic placards, education applicants are attracted to an active, specifically focused on their activities. Electronic interactive placards allow you to choose the optimal pace of teaching, control and adjust the course of mastering the educational material, and the result of the work can be seen almost immediately, and not after a while. In addition, education applicants have the opportunity to implement their own methods and techniques of teaching the material. It is determined that one-level placards are usually a working area with the necessary training material and a set of different interactive elements. Multi-level interactive placards consist of several single-level, as well as two-level placards. The advantages of using interactive placards for organization of collective cognitive activity of students (students) have been proved. The results of the study can serve as the basis for further study of the problem of designing interactive e-placards. We consider a promising study of the methodology of using software for the creation of interactive electronic placards.